Note on mating behavior of the edible-nest swiftlet (Aerodramus fuciphagus) - Othman, Azman (Department of Wildlife and National Parks - Perhilitan, 2008)
Study on the mating behavior of the Edible-nest swiftlets (Aerodramus fuciphagus) using direct observation was conducted at a bird house in Sepang, Sselangor on the 26th until 21st December 2008. Photographs of the activities were taken and sorted according to mating sequences. There were- four mating stages identified in this study namely: chasing, approaching, mating and separating. Mating behavior in the air took about 15 minutes.